Heavy metals in biotic and abiotic components in Seri Serdang lake in different weather conditions - Abdul Rahman, Khairunnisa (2018)
The threat from heavy metal pollution to living organisms is real and heavy metal is known to cause health issues to human particularly. In Malaysia most of the heavy metal studies mainly on the heavy metal content in the tissues but seldom involving the food chain and food web. Therefore a study was carried out to assess the concentration of heavy metals (lead, cadmium, nickel, copper, iron and zinc) in abiotic (water, sediment, rain water) and biotic (phytoplankton, Vallisneria, Valvata tricarinata, small and big Oreochromis mossambicus, Chironomid larvae and Ardea alba) components in Seri Serdang Municipal Lake. These components were collected from the inlet (other sources channel into the lake) and outlet (lake water channel to river) of this lake in three different weather conditions which are dry, wet and mixed season. After acid digestion, analysis of metal concentration in these components were assessed by using atomic absorption spectrophotometer (AAS). The highest concentration of metal during dry weather conditions for rain water and lake water were Fe and Ni with concentration of 0.24 μg/g and 5.02 μg/g. Contrast with sediment that has highest concentration of metal (Fe) in wet weather conditions with concentration of 2015.99 μg/g. In biotic components, aquatic macrophytes, Vallisneria is the highest component that has high value of metals; Fe, than other components with concentration of 1775.81 μg/g during dry weather conditions. Furthermore, the highest concentration of metals in big Oreochromis mossambicus was Fe with value of 335.18 μg/g during weather conditions. Ardea alba also has highest concentration of metal in dry weather condition which was Fe (166.75 μg/g). In general the results showed that heavy metal in the dry conditions were significantly higher than wet and mixed condition, while components from inlet have higher concentrations than the outlet. The sequence of metal concentration in sediment at inlet point during dry condition was Fe>Zn>Cu>Ni>Pb>Cd. From the food web of this lake, three of food chain were identify. In food chain 1, from Vallisneria to small and big Oreochromis mossambicus are mostly the metals experiencing dilution in both inlet and outlet point. However for non essential metals; Pb, Ni and Cd have the higher value especially Cd and most of it occurred at the outlet point during dry, wet and mixed conditions. Furthermore, from small and big Oreochromis mossambicus to Ardea alba, all metals concentration were increased at inlet and outlet point for all these weather conditions. This magnified pattern in Ardea alba also occurred in food chain 2 and 3 for dry, wet and mixed weather conditions respectively. Confirmation with experimental data showed the higher organism (Ardea alba) in trophic level in food chain has been carrying the metals from lower level by biomagnification process. In actual ecosystem or environment, biomagnification and biodilution can happen concurrently or sequentially affecting the relationship and distribution pattern. The concentration of metals were significantly higher during dry weather conditions compared to the other weather conditions. Water temperature has some affects on aquatic organisms; high water temperatures can increase solubility and therefore toxicity of certain compounds. Therefore when the heavy metals in Seri Serdang Lake ecosystem increased biomagnification process through food chain/food web caused the organism at the higher trophic level to have elevated heavy metal.